Frame-composite mesh: A new method to treat complex unstable flail chest: A case report - Chittawatanarat K. (2017)
A middle aged Thai male was admitted suffering from a severely unstable flail chest caused by an elephant having trampled on the upper right part of his chest. He failed to respond to conservative treatment and conventional surgery could not be performed due to the bony defect in the chest wall. Consequently, a frame-composite mesh was designed and constructed in close collaboration with Chiang Mai University's Biomedical Polymers Technology Unit. After implantation, the patient could be taken off a mechanical ventilator successfully without any adverse event. Two weeks after surgery, he was found to have good pulmonary function and so the clinical outcome was judged to be successful.